INFLUENCE OF RISK FACTORS FOR DISEASE PROGRESSION ON TREATMENT RESULTS IN PATIENTS WITH PROSTATE CANCER - R. M. Isargapov; M. O. Vozdvizhensky; A. L. Gorbachev (Сибирский онкологический журнал)
The purpose of the study was to optimize treatment of patients with prostate cancer at high risk of disease progression using a quantitative assessment of risk factors and the treatment method.Material and methods. Immediate outcomes were analyzed in 107 patients with pt3a-bn0m0g2–4 prostate cancer, who were treated in samara regional clinical oncological dispensary between 2010 and 2012. All patients were divided into 2 groups. Group i patients underwent surgery alone and group ii patients underwent surgery followed by radiation therapy. All patients were at high risk of disease progression according to the d’amico classification. Onlyone risk factor was identified in 64 patients, two risk factors in 37 patients, and three risk factors in 6 cases. The overall survival, cancer-specific survival and disease-free survival were analyzed.Results. In cases with one and two risk factors, the overall, disease-free and cancer-specific survival rates were statistically higher than in cases with three risk factors in the entire cohort (p<0.05). In the subgroups with one, two, and three risk factors, there were no statistically significant differences in overall and cancer-specific survival rates (p>0.05). Disease-free survival rates in the presence of one factor were not statistically different (p=0.920). In the presence of two and three factors, the relapse-free survival rates were statistically higher in group ii patients (surgical with adjuvant radiation therapy, p=0.049, p=0.025).Conclusion. The presence of three risk factors significantly increased the likelihood of a poor prognosis compared with one or two factors. Adjuvant radiation therapy improved survival rates in prostate cancer patients.